2022
DOI: 10.1128/spectrum.02296-21
|View full text |Cite
|
Sign up to set email alerts
|

Marine Sponge Endosymbionts: Structural and Functional Specificity of the Microbiome within Euryspongia arenaria Cells

Abstract: Sponges host abundant microbial symbionts that can produce an impressive number of novel bioactive metabolites. However, knowledge on intracellular (endosymbiotic) microbiota is scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…The predominant approach to study sponge holobiont was 16S. However, several studies featured shotgun metagenomic approaches, which shed light on sponge microbiome metabolic potential ( Table 1 , Yang et al, 2022 ; Moreno-Pino et al, 2020 , 2021 ). Sampling has been performed in all continents from the Southern Hemisphere, but mainly in Western Antarctic Peninsula ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant approach to study sponge holobiont was 16S. However, several studies featured shotgun metagenomic approaches, which shed light on sponge microbiome metabolic potential ( Table 1 , Yang et al, 2022 ; Moreno-Pino et al, 2020 , 2021 ). Sampling has been performed in all continents from the Southern Hemisphere, but mainly in Western Antarctic Peninsula ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence suggests that sponge microbiome is similar at the phylum level between species in the Southern and Northern Hemispheres ( Taylor et al, 2007 ). In the Southern Hemisphere, sponge microbiome is characterized by several core bacterial phyla, including Proteobacteria, Bacteroidetes, Actinobacteria, Verrucomicrobia, Acidobacteria, and Cyanobacteria ( Rodríguez-Marconi et al, 2015 ; Matcher et al, 2017 ; Cárdenas et al, 2018 , 2019 ; Savoca et al, 2019 ; Papale et al, 2020 ; Happel et al, 2022 ; Ruocco et al, 2021 ; Yang et al, 2022 ). Interestingly, Thaumarchaeota is the only archaea phylum associated with sponges, yet its association is consistent across several species ( Brochier-Armanet et al, 2008 ; Sacristán-Soriano, Pérez Criado & Avila, 2020 ; Moreno-Pino et al, 2020 ; Steinert et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genus Burkholderia has demonstrated significant differences in CEs ( 50 ). Pseudomonas belongs to the lipase-producing bacteria and has been found only in the endosymbiotic flora, while Pseudomonas also shows a greater abundance inside the cell ( 51 ). Follow justly, Pseudomonas exhibited a significant difference in the number of CEs between LA and SA habitats.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several studies investigating the functional gene repertoires of sponge holobionts (6)(7)(8)(9), there are relatively few studies that have interrogated the transcriptional profiles of these systems (10)(11)(12), and none focussing on bacterial symbionts at the genomeresolved level. A functional profile based on differential expression of genes of the HMA Xestospongia muta sponge holobiont was generated and showed that the associated bacteria had increased levels of transcripts associated with amino acid biosynthesis, while the host sponge transcribed genes for amino acid catabolism, suggesting a metabolic exchange between host and microbes (13).…”
Section: Introductionmentioning
confidence: 99%